Poor health, poor agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Growing our food is often bad for our health, just as poor health hampers us in growing our food. And defeating diseases such as malaria can clash with agricultural practice. In the tail of a challenge, the sting of a dilemma.We can feel it each...